Risk Factors for Occupational Injuries among Solid Mineral Miners in OSE Local Government of Ondo State, Nigeria - Kareem, Adesola; Owoeye-Lawal, Oluwatosin; Aro, Adewale; Kareem, Abiodun; Lawal, Opeyemi; Adewale-Aro, Olaide (International Journal of Occupational Safety and Health, 2022)
Introduction: The mining industry is known to have a high incidence rate of fatal injuries hence, the knowledge of the risk factors of injury is important. The risk factors of occupational injury are important in the interplay between work and health, and the knowledge of the risk factors can be used in planning preventive measures. The study was done to determine the risk factors for occupational injuries among solid mineral miners. Methods: This was a descriptive cross-sectional study. Consenting staff completed the pretested self-administered questionnaire. Data were analyzed using descriptive and inferential statistics and p ≤ 0.05 was considered significant. Results: A total of 120 workers were recruited with 109 (90.8%) males and 11 (9.2%) females leading the male to female ratio of 9.9:1. The age range was 18-48 years with a mean of 28.9 (5.8) years. More than one-third (35.0%) had a tertiary level of education. Seventy-two (60.0%) had good knowledge of the occupational injury, and it was associated with the level of education (p<0.001) and occupational injury (p<0.001). About 60.8% have had an occupational injury while inhalational injury (30.0%) was the highest type of injury. Hands (34.5%) were the most affected part of the body even though hand gloves (85.8%) were the most common personal protective equipment used. The factors associated with an occupational injury were age, length of services and job tasks. The predictor of occupational injury was the length of service. Conclusion: The respondents had good knowledge of the occupational injury and the major risk factors of occupational injury were the length of services, job tasks and age of respondents of this study.